Writings on the wall : a final year project book - Cheng, Si Min (Nanyang Technological University, 2021)
An introspection to the AY20/21 FYP Thesis Film, Writings On The Wall. This FYP Book contains reflections, research, and other forms of hard work that were put into the creation of the short film.